2014
DOI: 10.1139/cjpp-2014-0078
|View full text |Cite
|
Sign up to set email alerts
|

Combined metoprolol and ascorbic acid treatment prevents intrinsic damage to the heart during diabetic cardiomyopathy

Abstract: Metabolic disturbances and oxidative stress have been highlighted as potential causative factors for the development of diabetic cardiomyopathy. The β-blocker metoprolol is known to improve function in the diabetic rat heart and ameliorates the sequelae associated with oxidative stress, without lowering oxidative stress. The antioxidant ascorbic acid is known to improve function in the diabetic rat heart. We tested whether a combination of ascorbic acid and metoprolol treatment would improve function further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Autoantibodies against the β1 receptor could be a predictor for left ventricular hypertrophy for T2DM patients with hypertension (50,51). Treatment with metoprolol could inhibit intrinsic damage to the heart during diabetic cardiomyopathy (52). Several studies indicated that use of beta-blockers, such as bisoprolol, did not aggravate glycemic control, lipid profile or albuminuria status in T2DM patients with SHF (53,54).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibodies against the β1 receptor could be a predictor for left ventricular hypertrophy for T2DM patients with hypertension (50,51). Treatment with metoprolol could inhibit intrinsic damage to the heart during diabetic cardiomyopathy (52). Several studies indicated that use of beta-blockers, such as bisoprolol, did not aggravate glycemic control, lipid profile or albuminuria status in T2DM patients with SHF (53,54).…”
Section: Treatmentmentioning
confidence: 99%
“…Metoprolol and bisoprolol may inhibit the expression of c-fos through regulating the PKC-δ signaling pathways. Although there is little evidence of the effects of signal transduction pathways of beta-blockers on the expression of c-fos, one study showed that bisoprolol, especially at high doses, could increase the survival rate of hypertensive diastolic heart failure model of rats, at least partly through the alleviation of inflammatory changes (interleukin-1β, transforming growth factor-β1 and monocyte chemoattractant protein-1) and oxidative stress (reactive oxygen species production and nicotinamide adenine dinucleotide phosphate oxidase activity) (52). Moreover, isoproterenol (ISO)-induced heart failure could be inhibited by a Rho-associated protein kinase (ROCK) inhibitor, fasudil, which suppressed isoproterenol-induced JNK activation, translocation of ERK to the nucleus, and increased expression of c-fos and c-jun through RhoA/ROCK.…”
Section: Treatmentmentioning
confidence: 99%
“…Vitamin C has the ability of scavenging free radicals. This vitamin has cardioprotective properties, which were demonstrated to reduce oxidative damage in diabetic rats and during ischemia/reperfusion (I/R)-injury [12,13] . In some studies, vitamin C improved myocardial stunning and enhanced left ventricular function [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its capability to scavenge free radicals, vitamin C also promotes the differentiation of embryonic and pluripotent stem cells into cardiac myocytes [ 33 , 34 ]. Vitamin C has cardioprotective properties, which were demonstrated in rat models, where vitamin C reduced oxidative damage in diabetic rats [ 83 ] and during I/R-injury [ 84 ]. Vitamin C improved myocardial stunning and increased left ventricular function in some animal studies, however, other animal studies showed no effect of vitamin C and some only in combination with other antioxidants [ 49 ].…”
Section: Influence Of Vitamin C On Organ Systems In Cardiac Surgermentioning
confidence: 99%